Integrating Transaction Cost and Institutional Theories: Toward a Constrained-Efficiency Framework for Understanding Organizational Design Adoption - Roberts, Peter W.; Greenwood, Royston (Academy of Management Review, 1997)
Transaction cost and institutional theories are integrated in order to enhance understanding of the process by which entities adopt new organizational designs. By grafting cognitive and institutional constraints into the comparative-efficiency framework favored by transaction cost theorists, theorists using the constrained-efficiency framework demonstrate both how efficiency-seeking organizations may be biased in favor of current designs and those that are legitimated within their institutional contexts. The article closes by overlaying the constrained-efficiency framework onto the discussion about the evolution of the M-form of organization, as well as suggesting empirical and simulation strategies consistent with the logic of the constrained-efficiency framework.